Pengaruh inflasi, nilai tukar rupiah per dollar Amerika, harga minyak mentah dunia dan indeks harga saham gabungan terhadap harga emas di Indonesia - Kesarditama, Fadhel; Haryadi, Haryadi; Vyn Amzar, Yohanes (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the trend of macroeconomic variables and gold prices in Indonesia and to determine the effect of macroeconomic variables on gold prices in Indonesia. This study uses a quantitative approach. The data used is secondary data from January 2014-December 2019. The analytical tools and techniques used are trend analysis with a linear trend approach and multiple linear regression models using the Ordinary Least Square method. The five research variables that were processed showed that there were differences in the direction of the data trend. Where the variables of Gold Price, Exchange Rate, and Composite Stock Price Index show a positive trend, while the variables of Inflation and World Crude Oil Prices show a negative trend. Furthermore, the variables of Exchange Rate, world Crude Oil Price, and Composite Stock Price Index show a positive and significant influence on the Gold Price in Indonesia. While the inflation variable shows a negative and significant effect on the Gold Price in Indonesia. Keywords: Inflation, foreign exchange,crude oil prices, idx composite and gold prices